Partisipasi Masyarakat Dalam Menanggulangi Bencana Banjir di Perumahan Bukit Sawangan Indah Kelurahan Duren Mekar Kecamatan Bojong Sari Kota Depok - Aisyah Nur Rahma; Dini Gandini Purbaningrum (Populer: Jurnal Penelitian Mahasiswa, 2024)
The flood management program at the Bukit Sawangan Indah Housing Complex is an effort and method to overcome flood disasters when water overflows and the inability of the embankments and the Angke river sheet pile to accommodate water deliveries from Bogor, West Java. The flow of the Kali Angke River which is right at the Bukit Sawangan Indah Housing Complex is the flow and end point of the Kali Angke Channel. So all the problems with the flow of the Kali Angke river are centered on the Bukit Sawangan Indah housing complex because the position of the housing complex is an estuary. The aim of this research is to determine the level of community participation in overcoming flood disasters in the Bukit Sawangan Indah Housing Complex, Duren Mekar Village, Bojong Sari District, Depok City, from all sides and how to deal with it. The steps in efforts to overcome flood disasters are starting to seek aspirations and attracting community sympathy in protecting and preserving the surrounding environment, increasing community awareness, then instilling the values of deliberation and consensus, fostering the values of mutual cooperation and cooperation, mingling and helping fellow local residents to maintain one condition and another. In realizing community participation in overcoming the threat of flooding in the Bukit Sawangan Indah Housing Complex, Duren Mekar District, Depok City, the author used descriptive qualitative research. Even though this research has obstacles in its efforts to overcome, efforts are being made immediately to preserve the environment in the future. With awareness of the challenges and commitment to continuous improvement, the collaboration of all parties, namely the Bukit Sawangan Indah housing community itself, RT/RW management, youth organization management, firefighters and the Tagana team has the potential to create a more efficient and responsive environment in the improvement process for dealing with flood disasters.